2007
DOI: 10.1292/jvms.69.881
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Deaminase Activity in Cats Infected with Feline Immunodeficiency Virus

Abstract: ABSTRACT. Adenosine deaminase (ADA), an enzyme involved in purine metabolism, has been shown to be of clinical importance in several diseases in humans. To investigate whether ADA is of any clinical significance in cats, plasma adenosine deaminase (P-ADA) and T cell adenosine deaminase (T-ADA) activities were measured in feline immunodeficiency virus (FIV) negative and positive cats. The AIDS-related complex (ARC) group showed a significant elevation in P-ADA activity compared to the asymptomatic carrier (AC),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Lymphocyte activation following FIV infection is shown by increased germinal center activity in lymph nodes and high expression of T and B cell activation markers [26,31]. We also observed that adenosine deaminase in T cell and plasma, which is released during T cell activation, was significantly elevated in FIV-infected cats in the ARC phase [7]. Persistent immune activation in HIV and FIV infection results in progression to AIDS [6,8,23].…”
mentioning
confidence: 51%
“…Lymphocyte activation following FIV infection is shown by increased germinal center activity in lymph nodes and high expression of T and B cell activation markers [26,31]. We also observed that adenosine deaminase in T cell and plasma, which is released during T cell activation, was significantly elevated in FIV-infected cats in the ARC phase [7]. Persistent immune activation in HIV and FIV infection results in progression to AIDS [6,8,23].…”
mentioning
confidence: 51%